Things my son needs to know about the world [large type] - Backman, Fredrik, 1981- (Thorndike Press Large Print core, 2019)
"Things My Son Needs to Know About the World collects the personal dispatches from the front lines of one of the most daunting experiences any man can experience: fatherhood. As he conveys his profound awe at experiencing all the "firsts" that fill him with wonder and catch him completely unprepared, Fredrik Backman doesn't shy away from revealing his own false steps and fatherly flaws, tackling issues both great and small, from masculinity and mid-life crises to practical jokes and poop. In between the sleep-deprived lows and wonderful highs, Backman takes a step back to share the true story of falling in love with a woman who is his complete opposite, and learning to live a life that revolves around the people you care about unconditionally. Alternating between humorous side notes and longer essays offering his son advice as he grows up and ventures out into the world, Backman relays the big and small lessons in life"--